التحول إلى موازنة البرامج في إطار الإصلاح الميزانياتي بالجزائر - بن قويدر حياة (جامعة الوادي University of Eloued, 2023)
تطرقنا في هذه الدراسة إلى موازنة البرامج والأداء كنظام لإعداد الموازنة العامة للدولة يهتم أساسا بقياس الأداء من أجل ضمان نجاعة الأموال العمومية والجزائر كغيرها من الدول العالم بدأت في إصلاحات النظام الموازاناتي بالإنتقال التدريجي نحو موازنة البرامج والأداء من أجل الوصول إلى فعالية التسير و تحقيق كفاءة في الإنفاق إضافة إلى تحليل أهم ما جاء به القانون العضوي 18-15 المتعلق بقوانين المالية في مجال تطبيق موازنة البرامج والأداء بشكل فعال يمكن من تحقيق الأهداف المرجوة من هذه الإصلاحات. وخلصت الدراسة إلى التوصل أن الجزائر رغم بداية الإصلاح الميزانياتي من 2005 و إصدار القانون العضوي المتعلق بقوانين المالية سنة 2018 إلا أنها تعتبر متأخرة في تطبيق موازنة البرامج والأداء الذي سيبدأ العمل بها ابتداء من2023 رغم السلبيات التي تتصف بها موازنة البنود، وفي الأخير أوصت الدراسة بضرورة تدارك النقائص في أليات تطبيق موازنة البرامج والأداء سواء فيما تعلق بالجانب التشريعي أو الجانب الإجرائي و ذلك بهدف تحقيق الإصلاح والوصول إلى رفع الأداء في القطاع العام The study aims to identify the budgeting of programs and performance as a system for the preparation of the State's general budget, which is primarily concerned with measuring performance in order to ensure the effectiveness of public funds. Algeria, like other countries around the world, has begun to reform the budgetary system by gradually moving towards the budgeting of programs and performance, as well as analysing the most important provisions of the 18-15 Organic Act on Financial Laws in order to effectively implement program budgeting and performance. The study concluded that despite the start of budgetary reform from 2005 and the enactment of the Organic Law on Finance Laws in 2018, Algeria is considered to be in arrears in the application of the program and performance budget, which will be introduced from 2023 despite the shortcomings in the budget of the items;lastly, the study recommended that deficiencies in program budgeting and performance mechanisms should be remedied in terms of both the legislative and the procedural aspects, with a view to achieving reform and achieving higher performance in the public sector.
Transition to program budgeting as part of Algerian budget reform
Keywords: موازنة البرامج والأداء; القانون العضوي 18-15; الإصلاح الميزانياتي في الجزائر; Program and Performance Budget; the organic law 18-15; Algeria's budgetary reform